The Impact of Dams on Regional Economic Growth: Empirical Evidence from National Strategic Projects in Indonesia - Muhammad Nur Hidayat; Irfani Fithria Ummul Muzayanah (Jurnal Ekonomi dan Studi Pembangunan, 2025)
This study analyzes the impact of dam operations on regional economic growth in Indonesia by applying the economic base theory within a Difference-in-Differences (DiD) framework. The panel dataset covers 259 regencies/municipalities surrounding 48 National Strategic Project (PSN) dams, categorized into core regions, immediate neighbors, and second-tier neighbors over the 2018–2023 period. The results indicate that dam operations significantly increase Gross Regional Domestic Product (GRDP) in agrarian regions, with estimated gains of IDR 2.6 trillion in core regions and IDR 2.4 trillion in immediate neighbors, while effects remain statistically insignificant in non-agrarian regions. Trend analysis indicates a declining positive impact in agrarian core regions, an increasing negative impact in non-agrarian core regions, and a strengthening positive impact in neighboring areas. These findings underscore the relevance of economic base theory in explaining spatial variations of dam impacts and provide insights for developing more contextual and sustainable strategies to maximize the benefits of dam infrastructure.